2014
DOI: 10.1159/000353160
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Reactions in Patients with Chronic Hepatitis C Treated with Peginterferon and Ribavirin

Abstract: Background/Objective: Peginterferon alfa and ribavirin could cause various cutaneous reactions. Treatment-related cutaneous reactions are common, and treatable complications can contribute to the treatment discontinuation. Methods: We performed a 6-year prospective study of cutaneous reactions in 271 patients with chronic hepatitis C treated with peginterferon and ribavirin. Results: Cutaneous reactions of mild to moderate degree were seen in 36 (13.3%) patients: localized cutaneous reactions in 7 (2.6%) patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
0
12
0
1
Order By: Relevance
“…In some of the studies, skin lesions were resolved without discontinuation of therapy in the majority of patients (9,10,11). In one of these studies performed by Patrk and colleagues, it is pointed that the number of patients followed without discontinuation of therapy was less than the number of those continued therapy (9). In our second case, skin lesions recovered without discontinuation of anti-HCV treatment and with using symptomatic treatment, including antihistamines and topical steroid.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In some of the studies, skin lesions were resolved without discontinuation of therapy in the majority of patients (9,10,11). In one of these studies performed by Patrk and colleagues, it is pointed that the number of patients followed without discontinuation of therapy was less than the number of those continued therapy (9). In our second case, skin lesions recovered without discontinuation of anti-HCV treatment and with using symptomatic treatment, including antihistamines and topical steroid.…”
Section: Discussionmentioning
confidence: 56%
“…This reason gives rise to thought that skin eruptions might be seen more frequent due to ribavirin. In some of the studies, skin lesions were resolved without discontinuation of therapy in the majority of patients (9,10,11). In one of these studies performed by Patrk and colleagues, it is pointed that the number of patients followed without discontinuation of therapy was less than the number of those continued therapy (9).…”
Section: Discussionmentioning
confidence: 99%
“…A distancia de éste se ha descrito la aparición de sarcoidosis, urticaria, fenómeno de Raynaud, alopecia y la exacerbación de dermatosis previas como la dermatitis atópica, la psoriasis o el lupus eritematoso 3 . La ribavirina puede producir reacciones de fotosensibilidad [4][5][6] . Con el telaprevir es muy frecuente la aparición de anemia por lo que el control hematológico mediante un hemograma es primordial 2 .…”
Section: Discussionunclassified
“…LP has been reported to develop or worsen with interferon therapy, largely in the context of hepatitis C. 4 , 5 , 6 A prospective study found that of 67 patients with hepatitis B and 45 patients with hepatitis C treated with recombinant interferon α (IFN-α), 1 patient with hepatitis B and 2 with hepatitis C developed LP. 5 Another study of 271 patients with hepatitis C treated with peginterferon and ribavirin found an exacerbation of lichen planus in 1 patient.…”
Section: Introductionmentioning
confidence: 99%